Pitfalls in the Histological Diagnosis of Inflammatory Bowel Disease on Colorectal Biopsies - DA Malatjalian (Canadian Journal of Gastroenterology)
Histopathological examination of appropriate colorectal biopsy specimens allows accurate identification of chronic inflammatory bowel disease in the majority of cases. Pitfalls, however, appear because overlapping histological features occur among the various forms of colitis or because a specific form of colitis may exhibit incomplete expression of its characteristic features. Pitfalls can be minimized if the histological findings are considered in the context of all other clinical and investigative data.